(Un)masking the reign of terror in Nigeria: armed banditry and state complacency - Okoli, Al Chukwuma (Armed banditry in Nigeria, 2024)
Nigeria is not the only country challenged by dire national security threats. However, the attitude of the Nigerian state towards the prevailing challenges of national security has left a lot to be desired. The government and its national security architecture are critically embattled as violent non-state actors (VNSAs) aggrandize in criminal opportunism and impunity. The underworld, masquerading as terrorists and armed bandits, has successfully negated the territoriality of the state, creating spheres of competitive control for themselves within the country’s contested jurisdiction. Curiously, the state is negotiating sovereignty with these forces through questionable amnesty deals, ransom-making and tradeoffs, as well as outright complacency. This chapter interrogates this situation from the standpoint of the apparent helplessness of the Nigerian state in the face of the scourge of armed banditry in the country. Relying on a qualitative analysis that is anchored on a state functionality framework, the chapter posits that the prevalence of banditry in Nigeria today derives from declining capacity and legitimacy of the state in that context to assert and enforce its will authoritatively. The chapter contends that until the receding Nigerian state reinvents its coercive and affective ompetencies to effectively govern, it will continue to negotiate sovereignty with VNSAs, including the bandits.